2020
DOI: 10.3390/antiox9080714
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Psychotropic Drugs: From Clinical Evidence to In Vitro and In Vivo Assessment and toward a New Challenge for in Silico Molecular Design

Abstract: Due to high oxygen consumption, the brain is particularly vulnerable to oxidative stress, which is considered an important element in the etiopathogenesis of several mental disorders, including schizophrenia, depression and dependencies. Despite the fact that it is not established yet whether oxidative stress is a cause or a consequence of clinic manifestations, the intake of antioxidant supplements in combination with the psychotropic therapy constitutes a valuable solution in patients’ treatment. Anyway, som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 168 publications
(253 reference statements)
0
36
0
Order By: Relevance
“…This substrate was chosen as a model also because the corresponding elimination product, morpholine, represents an outstanding example of pharmacologically relevant moiety. Interestingly, it can be found in drugs acting on CNS (e.g., in the antidepressants reboxetine and viloxazine and in the withdrawn stimulant phenmetrazine), and which are used to treat pathologies where oxidative stress has been demonstrated to play a role on disease onset and progression [ 28 , 29 ]. More in detail, compound 3 was dissolved in deuterated water and reacted with 1.2 equivalents of hydrogen peroxide at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…This substrate was chosen as a model also because the corresponding elimination product, morpholine, represents an outstanding example of pharmacologically relevant moiety. Interestingly, it can be found in drugs acting on CNS (e.g., in the antidepressants reboxetine and viloxazine and in the withdrawn stimulant phenmetrazine), and which are used to treat pathologies where oxidative stress has been demonstrated to play a role on disease onset and progression [ 28 , 29 ]. More in detail, compound 3 was dissolved in deuterated water and reacted with 1.2 equivalents of hydrogen peroxide at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of several mechanisms is perfectly in harmony with the growing interest towards the development of multi-target-directed ligands (MTDL) that take advantage of synergistic pharmacological effects [ 62 ]. Moreover, depending on their chemical structures, the neuroprotective effect of several natural and nature-inspired compounds, as outlined above, is also connected with their activity against reactive oxygen species (ROS) and inflammation [ 63 , 64 , 65 , 66 ]. In this connection, it was also reported that natural PDE inhibitors, by increasing cGMP levels, reduce the production of IL-6 and TNF-α [ 23 ].…”
Section: Conclusion: the Perspective Of The Medicinal Chemistmentioning
confidence: 99%
“…This suggests that risperidone and other AAPs can decrease OS in glaucoma [ 148 , 152 ]. Among AAPs, clozapine and olanzapine can also decrease OS [ 148 , 153 ]. Nevertheless, few studies have investigated the relationship between AAPs and the WNT/β-catenin pathway in glaucoma by acting OS and thus, the ROS production.…”
Section: Lithium and Aaps In Glaucomamentioning
confidence: 99%